The effect of some Rehabation exercises on the abdominal circumference after caesarean operation - Idaan, Hadeer; Hosni, Ghayda (Journal of Physical Education, 2019)
The importance of this research lie on the work to rehab the abdominal muscles to its shape before pregnancy or close to through exercises that focused on abdominal muscles, the research problem was displayed through multiple cases of Caesarean operations in our society and that led to a marked abnormalities on pregnant belly after birth, and one of its manifestations is sag in these muscles and increase their surroundings than previously pregnancy in addition to other symptoms that may be associated with that weakness in this area, and the research sample represented by (10) women, all of whom health status: free blood pressure, diabetes, anemia disease as well as physically fit, that they do not show any obesity signs or thinness, aged between (30-35 years), and all of them had the first birth by caesarean operation. The concluded that the program’s has positive effect on weight because it lowering body weight and the program has positive effect in abdominal circumference, the researchers recommended to work on other research samples for big sample and ages, and deferent cultural or less educational, and provide another means such as training stationary bike and a treadmill, and a.vibration machines... etc